Ozaveščanje in promocija trajnostnega razvoja energetike in uporabe obnovljivih virov energije - Papler, Drago (IB revija (Ljubljana), 2010)
This paper investigates in what degree consciousness, promotion and educational activities contribute to knowledge of sustainable development of energetic and use of renewable sources of energy as well knowledge about climatic-energy package of the European Union. Into the survey analysis are included target groups from social and sciences, electro energy and energy management. We focus on the opinions of the students from social sciences. The survey data are analysed by summary statistics of mean values of the respondents, correlation and multivariate factor analysis. Among the sources of energy in sustainable development of energetic and use of renewable sources of energy with support policies are found three common factors: consciousness, educational activities, promotion and support for energetic sources; commitments for more efficient energetic policy and use of energy sources; and natural potentials of renewable sources of energy. These are the factors to which should be given a greater attention in management of development of the Slovenian energetic economy within the climatic-energetic policy of the European Union by the year 2020.
Keywords: sustainable development; trajnostni razvoj; energetika; energetski viri; obnovljivi energetski viri; ozaveščanje